What's New in the Clinical Management of Disorders of Social Cognition?. Issue 1 (6th February 2017) - McDonald, Skye
Abstract : Social cognition refers to the ability to use social cues to infer the meaning and intentions behind the behaviour of others in order to respond in a socially adaptive manner. It is increasingly recognised that disorders of social cognition, including problems with emotion perception, theory of mind, conversational inference, morality judgements, decision making and social inhibition, characterise many developmental and psychiatric disorders and are highly relevant to many with acquired brain injuries or diseases, especially the frontotemporal dementias. This review provides an introduction and overview of the papers in this special edition on social cognition and places these in the context of other recent research. In doing so, several current issues in the clinical management of social cognition are delineated. Given that social cognition seems to be a sensitive predictor of psychosocial function, the assessment of social cognition is seen by many clinicians to be important although which profession is responsible is yet to be resolved. Issues in how social cognition are assessed are discussed, including the importance of context to social cognition, its interactive nature and the need to recognise influences such as family upbringing, gender and emotional state on social cognitive performance. There also needs to be development of tests that address all aspects of social cognition, including decision making and inhibition. Finally, this review discusses intervention research. Interventions are especially well developed in relation to schizophrenia, and less well developed in brain injury. These appear to be generally effective although treatments for emotional self-awareness are yet to be developed.